Konsentrasi Industri Pada Perekonomian Wilayah Di Jawa Timur - Alvazaki Ikbar Maulana; Dinda Widya Kumalasari; Verinda Yelanita; Galang Rambu A.; Muhammad Yasin (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
Industry concentration is centered on the number and size distribution of companies. In this case it can be said that the fewer the number of companies in the market, the level of industry concentration tends to be linked to the ability of sellers (producers) in the market. This can be a form of suppressing competition and coordinating price policies which tend to be high.